PENGELOLAAN SISWA PADA SEKOLAH BERBASIS AGAMA ISLAM - Nadjematul Faizah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2023)
The purpose of this research is to describe how students should be managed in religion-based schools, especially Islam. The research method is qualitative through a library study approach developed from Suharsimi Arikunto theory of management and Shafique Ali Khan's about students. Data collection techniques with utilization studies and data processing with reduction, data presentation and drawing conclusions. The results of the research: (1) management is a way of carrying out an organization's work program. (2) students are people who come to school to seek knowledge. (3) student management is the way schools regulate student work programs which are carried out in several ways: (a) student admission is carried out by tests of general intelligence on subjects and religion by tests on reading the Koran and knowledge of the pillars of Islam and faith. (b) placement of students by mixing smart and less intelligent students and placing them in classrooms according to gender. (c) student entry and return routes, not carried out in one door but distinguishing entrances for male and female students. (d) extracurricular programs: preachers, tahfidz and personality development of students through leadership, purification and cooking.